2021
DOI: 10.3390/ijms22084215
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Nutrition and Heart Rate Variability

Abstract: Heart rate variability (HRV) represents the activity and balance of the autonomic nervous system and its capability to react to internal and external stimuli. As a measure of general body homeostasis, HRV is linked to lifestyle factors and it is associated with morbidity and mortality. It is easily accessible by heart rate monitoring and gains interest in the era of smart watches and self-monitoring. In this review, we summarize effects of weight loss, training, and nutrition on HRV with a special focus on obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 74 publications
0
16
0
2
Order By: Relevance
“…The resting heart rate influences autonomic control, and a higher resting heart rate is indicative of reduced parasympathetic activity. 23 , 24 , 25 , 26 , 27 , 28 , 29 In the present study, the average resting heart rate of overweight individuals was 70 beats per minute. Also, CAF fluctuates throughout the day and varies according to different activities, the regulation of hormones and muscle mass in an individual.…”
Section: Discussionmentioning
confidence: 42%
“…The resting heart rate influences autonomic control, and a higher resting heart rate is indicative of reduced parasympathetic activity. 23 , 24 , 25 , 26 , 27 , 28 , 29 In the present study, the average resting heart rate of overweight individuals was 70 beats per minute. Also, CAF fluctuates throughout the day and varies according to different activities, the regulation of hormones and muscle mass in an individual.…”
Section: Discussionmentioning
confidence: 42%
“…Even though the BDI-score did not influence the present results, many studies reported a negative effect of depressive symptoms and other factors on HRV (Kemp et al, 2010). A more rigorous sampling that accounts for effects of depressiveness, and underor overweight (Peyser et al, 2021;Strüven et al, 2021) could benefit future studies. Furthermore, this study only looked at one video condition in comparison to questionnaires before and after the videos.…”
Section: Discussionmentioning
confidence: 62%
“…The level of high-density lipoprotein-cholesterol (HDL-C) was not changed in Gelug and Sakya monks (P BH adjusted > 0.05) or a bit lower in Nyingma monks (N vs Z: 1.13 ± 0.19 vs 1.32 ± 0.18, P BH adjusted = 0.046, ANCOVA, adjusted BMI, Supplementary Table 7). Despite being overweight or even obese, which is frequently comorbid with hypertension 30 and reduced HRV, 31 all three sects of monks have both blood pressure (all P BH adjusted > 0.05, Student's t-test or Mann-Whitney U test, Supplementary Table 7) and HRV measures (all P BH adjusted > 0.05, Mann-Whitney U test, Supplementary Figure 6) comparable to their matched Tibetan controls. In addition, we determined the relationship between the length of meditation and these clinical indicators.…”
Section: Resultsmentioning
confidence: 94%